Terracottas of Bengal : with special reference to Nadia - Ghosh, Sankar Prosad 1938- (New Delhi : B.R. Pub. Corp. ; New Delhi : Distributed by D.K. Publishers' Distributors, 1986)
Study, with reference to a district in West Bengal.
Includes index.
Includes bibliographical references and index.
Keywords: Terra-cotta -- India -- Nadia (District); Nadia (India : District) -- Civilization; Nadia (India : District) -- Antiquities; India -- Antiquities